2006
DOI: 10.1088/0957-0233/17/10/r01
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Boltzmann constant—status and prospects

Abstract: The present definition of the kelvin links the unit of temperature with a material property, namely the triple point temperature of water. It would be more consistent with the current approaches to other base units of the International System of Units to fix the value of the Boltzmann constant k, instead. This would rationalize the definition and make it separate from any technique of realization. Furthermore, it is needed to improve temperature measurement, particularly at temperatures far away from the tripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 63 publications
3
130
0
2
Order By: Relevance
“…Boltzmann's constant, the definition of the mol, and the universal gas constant are all interrelated through the identity R ¼ k B N A . Further improvement in the precision of experiments measuring either the refractive index or the dielectric constant of helium could lead to a redefinition of these quantities in terms of a standard which is based on the calculated helium polarizability (Stone and Stejskal, 2004;Fellmuth, Gaiser, and Fischer, 2006). Another atomic polarizability calculation with potential practical applications is that for the Be atom.…”
Section: Atomic Polarizability Calculationsmentioning
confidence: 99%
“…Boltzmann's constant, the definition of the mol, and the universal gas constant are all interrelated through the identity R ¼ k B N A . Further improvement in the precision of experiments measuring either the refractive index or the dielectric constant of helium could lead to a redefinition of these quantities in terms of a standard which is based on the calculated helium polarizability (Stone and Stejskal, 2004;Fellmuth, Gaiser, and Fischer, 2006). Another atomic polarizability calculation with potential practical applications is that for the Be atom.…”
Section: Atomic Polarizability Calculationsmentioning
confidence: 99%
“…4). Calculation of very precise physical properties of helium is of interest in the field of metrology to develop accurate calibration and pressure standards, to accurately compute the Boltzmann constant, and to improve acoustic gas thermometry [9][10][11][12][13][14]. Semi-classical virial coefficients up to fifth order have been computed for helium-4 by Shaul et al [15], and showed that first-principles properties could be evaluated with precision and accuracy that exceeds experiment.…”
Section: Tr Ementioning
confidence: 99%
“…The Consultative Committee for Thermometry (CCT) has considered the proposed definition and has emphasized the importance of the numerical value for the Boltzmann constant Methods that can contribute to the determination of the Boltzmann constant [48] could include dielectric gas thermometry, refractive index gas thermometry, Johnson noise thermometry and Doppler broadening thermometry. The most accurate published results to date come from the method of acoustic gas thermometry [49] and are plotted in figure 3.…”
Section: The Kelvinmentioning
confidence: 99%